To reflect on the function \( f(x) = (x + 2)^2 + 1 \), we'll first create a table of values by evaluating \( f(x) \) at \( x = 0 \), \( x = -1 \), and \( x = -2 \).
Evaluation of \( f(x) \)
Let's calculate \( f(x) \) for the specified values of \( x \):
-
For \( x = 0 \): \[ f(0) = (0 + 2)^2 + 1 = 2^2 + 1 = 4 + 1 = 5 \]
-
For \( x = -1 \): \[ f(-1) = (-1 + 2)^2 + 1 = 1^2 + 1 = 1 + 1 = 2 \]
-
For \( x = -2 \): \[ f(-2) = (-2 + 2)^2 + 1 = 0^2 + 1 = 0 + 1 = 1 \]
Table of Values
Now we can organize these values into a table:
| \( x \) | \( f(x) \) | |----------|------------| | 0 | 5 | | -1 | 2 | | -2 | 1 |
Reflection on the Origin
To reflect about the origin, we transform the values of \( f(x) \) from the table:
- The point \( (0, 5) \) reflects to \( (0, -5) \).
- The point \( (-1, 2) \) reflects to \( (1, -2) \).
- The point \( (-2, 1) \) reflects to \( (2, -1) \).
The resulting table for the reflection about the origin is:
| Reflected \( x \) | Reflected \( f(x) \) | |--------------------|----------------------| | 0 | -5 | | 1 | -2 | | 2 | -1 |
This table represents the new coordinates after reflecting the original points about the origin.